GAMBARAN KINERJA BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN PATI - Aeni, Nurul (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
Pati District has many villages whose potentials optimally have not developed yet. The existence of Village-owned enterprises (BUMDes) is expected to accelerating rural potentials then to elevating the economics. This study aimed (1) to portray the existing condition of BUMDes in Pati District and (2) to identify the factor hampered BUMDes development based on their performance evaluation. Qualitative and quantitative approaches were used together in this study. Observations were conducted on the data of 401 BUMDes based on the criteria released by The office of village community empowerment, regional population, and civil registration of Central Java Province. Then, the data of observation were confirmed by interviewing several relevant informants. Then, they were analyzed qualitatively and quantitatively to answer the research questions. This study concluded: (1) The development of BUMDes has not optimized yet that was proved by majority BUMDes were on a basic level. Saving and loan was the business unit chosen by the greater number of BUMDes, while only a few BUMDes run local potential-based businesses. (2) The obstacles of BUMDes management were found in all dimensions, namely the lack of capital and asset, unsystematic reporting and administration, weak effect of BUMDes on village community, inappropriate BUMDes management and business development, weak BUMDes legality. (3) Furthermore, those obstacles were rooted in the lack of capacity of BUMDes management, the current political constellation in the villages, lack of support from the village government, and business unit selection that was not based on a local potential review.